Deveti planet - Nered, Urša (Matrika, 2018)
The beginning of the paper reviews how mathematical predictions have led to discoveries in our Solar System in the past, specifically in case of Neptune. The following sections then examine the clustering of orbit parameters for distant Kuiper Belt objects and how it might be explained, with main focus being on explanation involving an as of yet undiscovered massive planet in the outer Solar System. At the end possible origins of the planet and estimated parameters derived from numerical simulations are considered.
Keywords: astronomija; astronomy; deveti planet; Kuiper belt; Kuiperjev pas; Osončje; planet nine; planeti; planets; Solar system